Digital Payments, Ecosystem Age, and Islamic Ethics in Cross-Provincial E-Commerce Revenue - Fajar Rakasiwi Syamsuddin (Institut Agama Islam Sunan Giri Ponorogo, 2026)
E-commerce revenue maturity varies across Indonesian provinces, but the factors driving this variation are poorly understood in isolation. This study examined the relationship between three digital ecosystem factors ecosystem age, digital payment intensity, and sales channel profiles and e-commerce revenue maturity using a cross-sectional design with secondary data from BPS Statistik E-Commerce 2023. Canonical correlation analysis revealed that the first canonical function was significant (Rc = 0.78, p < 0.001), indicating that the three factors collectively explained a substantial proportion of variance in revenue maturity. Social commerce channel configuration contributed most strongly, followed by digital payment intensity, while ecosystem age played a supporting role. From an Islamic ethics perspective, these results require that social commerce growth and digital payment expansion uphold 'adl (justice) by ensuring equitable access for underserved provinces such as Aceh and Central Kalimantan, amanah (trustworthiness) through transparent data and honest marketing, and maslahah (public interest) by prioritizing community welfare over platform profits. The study concludes that strengthening social commerce and digital payment infrastructure is essential for e-commerce revenue maturity, and that these factors operate as an integrated system grounded in Islamic commercial ethics.